Phosphate Flow between Hybrid Histidine Kinases CheA(3) and CheS(3) Controls Rhodospirillum centenum Cyst Formation - He, Kuang (Public Library of Science, 2013)
Genomic and genetic analyses have demonstrated that many species contain multiple chemotaxis-like signal transduction cascades that likely control processes other than chemotaxis. The Che(3) signal transduction cascade from Rhodospirillum centenum is one such example that regulates development of dormant cysts. This Che-like cascade contains two hybrid response regulator-histidine kinases, CheA(3) and CheS(3), and a single-domain response regulator CheY(3). We demonstrate that cheS(3) is epistatic to cheA(3) and that only CheS(3)∼P can phosphorylate CheY(3). We further show that CheA(3) derepresses cyst formation by phosphorylating a CheS(3) receiver domain. These results demonstrate that the flow of phosphate as defined by the paradigm E. coli chemotaxis cascade does not necessarily hold true for non-chemotactic Che-like signal transduction cascades.